Lenguaje oral en escolares de primer grado de primaria de zonas urbanas y urbano marginales de Ventanilla - Callao - Astudillo García, Rosa Maritza (2012)
The research was aimed to know the comparison between school oral language first grade of primary education in urban and urban fringe. The non-probability sample, consisted of 144 students from 6 years old, men and women of state educational institutions Ventanilla district - Callao. Test was applied Revised Oral Language Navarra (Plon-R) de Aguinaga, Armentia, Fraile, Olangua and Uriz (2005) adapted by Dioses (2006). Results indicate that differences between groups are not significant.